Mapping of Regional Economic Potential in South Aceh - Azra, Uliya; Al Karni, Wais; Maimun, Maimun (Majapahit Journal of Islamic Finance and Management, 2025)
Regional economic growth is one indicator of the success of a region's development. South Aceh Regency shows a positive economic growth rate, reflected in the increase in Gross Regional Domestic Product (GRDP) per capita. This study uses a quantitative approach with a descriptive research type to identify potential economic sectors in South Aceh Regency. The analysis methods used include Location Quotient (LQ), Shift Share, and Klassen Typology. Location Quotient is used to assess the relative advantages of economic sectors, Shift Share to identify sector contributions to growth, and Klassen Typology to classify sectors based on their characteristics. The results of the analysis show six leading base sectors: agriculture, forestry, and fisheries (LQ = 1.48); manufacturing industry (LQ = 2.22); government administration (LQ = 1.29); education (LQ = 1.29); health and social (LQ = 1.35); and construction (LQ = 1.10). Interpretation of these findings highlights the importance of the manufacturing industry sector, which has the highest LQ, as well as the strategic role of the government administration sector, even though it is not oriented towards the production of goods. To encourage sustainable economic development, several policy directions are suggested, such as the downstreaming of leading sectors, strengthening public services, improving human resources, and developing supporting infrastructure. With this strategy, leading sectors will not only become the current economic drivers but also the pillars of long-term economic transformation in South Aceh.